"Buyer's motivation" for online buying: an empirical case of railway e‐ticketing in Indian context. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – India has a big pool of internet savvy population that is not only accessing the internet but also buying online. Online shopping could be defined as the concept of buying and selling of goods over the internet. From the perspective of the seller, it is the attempt on the seller's part to attract and persuade the prospect to conduct the purchase decision‐making process, and ensure satisfaction and loyalty. From the perspective of the buyer, online purchase behavior is the degree to which consumers access, browse, shop and transact and repeat the behavior. With a revolution in the very basics of transaction from a physical store format to a non‐store one, the retail industry has begun to understand the indispensability of the internet as a medium of transaction. However, the rate of diffusion and adoption of the new phenomenon among consumers is still relatively low. With the internet advancing new opportunities, it is important to understand the factors that could motivate Indian consumers to indulge in online buying. This paper is a theoretical attempt at conceptualizing "motivation" as a construct, in the context of online buying and testing it empirically. The objective of the study is to explore the critical motivational factors that influence the online buying decision of people, and to establish their causal impact, if any, through developing an integrated model. Design/methodology/approach – The study, descriptive, diagnostic, and causal in nature, has been conducted in the context of online buying of railway tickets in India. In the first phase, a pilot survey was conducted on a sample of 100 users of the online railway reservation. After having tested the survey instrument for validity and reliability, the second phase of the study was conducted on a sample of 327 users of online railway reservation facilities. A series of multiple regressions analyses was conducted to determine the causal impacts of critical motivational parameters on online reservation of railway ticket by users in the Indian context. The analysis of demographics based on gender and age groups were also made to capture the cross‐comparisons of critical motivational attributes. Findings – The results were in expected direction and fulfilled the research aims of the current study. The factor analysis had grouped the items into nine constructs with 38 items. For analytical purposes, descriptive statistics were used through measures of central tendency and dispersion. The item total correlations to each construct were found significant. All the critical motivational constructs were found to have a significant impact on the intention of buyers of booking/purchasing railway tickets online in India. The analyses of demographics established that as far as gender is concerned, all the critical motivational attributes to online buying intention have no significant differences between men and women; however, for age groups it was observed that some of the attributes were found significant and others were not. Originality/value – Through identifying and empirically establishing critical motivational parameters in online reservation of railway tickets in Indian context across demographics, this study helps to understand what consumers expect from the online reservation facilities from the railways for their convenience and satisfaction. By examining the various dimensions explored and established in this study, the concerned authority can develop a better understanding of consumer needs and expectations. Academicians and researchers can use this study for assessing consumer motivation towards online reservation of railway tickets in Indian context, and identifying such attributes that would lead to favourable motivational disposition towards online reservation of railway tickets. The policy decision makers of railway authority may also use the findings of this study as a resource, while constructing, managing, and evaluating their marketing strategies in the Indian context. <ack> <x xml:space="preserve">Acknowledgements</x> The author is grateful to Mr Amitabha Datta, Junior Project Assistant at the Vinod Gupta School of Management at IIT Kharagpur, for his efforts that have helped the authors conduct the study. </ack>